Cyberspace : Ruang Publik Baru bagi Aktivitas Politik Muhammadiyah - Ahmad Sholikin (Profetik: Jurnal Komunikasi, 2019)
The presence of various political movements lately indicates a new appearance in the Indonesian middle class. Muhammadiyah in various previous studies has always been associated with the sociological class of the Indonesian middle class. Analysis of the middle class is always placed as "relaxed class" or "spoiled class". However, in recent cases, the class has transformed itself into a strong actor from the extra-parliamentary political arena that is able to influence political succession. The use of social media then becomes important in encouraging middle class political awareness to be an effective partisan class. This article uses the perspective of cyberactivism to elaborate more deeply on the potential of Muhammadiyah's political activism in the 2019 political year.